Capillary density and capillary-to-fibre ratio in vastus lateralis muscle of untrained and trained men - Zoladz, J A; Semik, D; Zawadowska, B; Majerczak, J; Karasinski, J; Kolodziejski, L; Duda, K; Kilarski, W M (Folia histochemica et cytobiologica, 2005)
Muscle fibre profile area (Af), volume density (Vv), capillary-to-fibre ratio (CF) and number of capillaries per fibre square millimetre (CD) were determined from needle biopsies of vastus lateralis of twenty-four male volunteers (mean +/- SD: age 25.4+/-5.8 years, height 178.6+/-5.5 cm, body mass 72.1+/-7.7 kg) of different training background. Seven subjects were untrained students (group A), nine were national and sub-national level endurance athletes (group B) with the background of 7.8+/-2.9 years of specialised training, and eight subjects were sprint-power athletes (group C) with 12.8+/-8.7 years of specialised training. Muscle biopsies of vastus lateralis were analysed histochemically for mATPase. Capillaries were visualized and counted using CD31 antibodies against endothelial cells. There were significant differences in the Vv of type I and type II muscle fibres in both trained groups, B (51.8%; 25.6%) and C (50.5%; 26.4%). However, in untrained group A that was treated as a reference group, the difference between Vv of type I and type II fibres was less prominent, nevertheless statistically significant (42.1%; 35.1%). There was also a significant difference in CF: 1.9 in group A and 2.1 in groups B and C. The number of capillaries per mm2 (CD) was 245 (group A), 308 (group B) and 325 (group C). Significant differences (P<0.05) in CF and CD, were found only between group A (1.9; 245) and both groups of trained men, B and C (2.1; 308 and 325). However, endurance athletes (group B), such as long-distance runners, cyclists and cross country skiers, did not differ from the athletes representing short term, high power output sports (group C) such as ice hockey, karate, ski-jumping, volleyball, soccer and modern dance.